Analysis Of Hygiene And Sanitation Feasibility At Masriah Catering, Banyuwangi Regency - Imaduddin, Davina Bilqis; Hutasoit, Jhonatan Rameldo; Husnina, Zida (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Hygiene and sanitation are essential aspects of ensuring food safety, particularly in large-scale catering services. This study aimed to analyze the level of hygiene and sanitation feasibility and identify areas of non-compliance at Masriah Catering, Banyuwangi Regency, based on the Regulation of the Minister of Health (Permenkes) No. 1096 of 2011. The study employed a descriptive observational method using an inspection checklist comprising five main assessment components with a maximum total score of 355 points. The results showed a feasibility level of 95.49% (categorized as Highly Feasible for Hygiene), reflecting effective hygiene–sanitation management implementation. However, 16 points were found to be non-compliant, particularly in aspects of personal hygiene, storage, packaging, and documentation. This emphasizes that personnel discipline and consistent field supervision are critical to maintaining hygiene standards. The study’s limitation lies in the absence of microbiological testing, meaning the findings describe administrative compliance and food handler behavior rather than actual food safety conditions. Conducted on a single catering unit, the study also limits generalizability. Nevertheless, these findings provide valuable insights into hygiene–sanitation implementation at the operational level and serve as an empirical basis for training and hygiene certification by local health authorities. Future studies should incorporate microbiological testing and behavior-based training interventions to strengthen result validity and support national food safety policies.